2018
DOI: 10.1186/s12889-018-5819-5
|View full text |Cite
|
Sign up to set email alerts
|

Where backyard poultry raisers seek care for sick poultry: implications for avian influenza prevention in Bangladesh

Abstract: BackgroundIn Bangladesh, backyard poultry raisers lack awareness of avian influenza and infrequently follow government recommendations for its prevention. Identifying where poultry raisers seek care for their ill poultry might help the government better plan how to disseminate avian influenza prevention and control recommendations.MethodsIn order to identify where backyard poultry raisers seek care for their ill poultry, we conducted in-depth and informal interviews: 70 with backyard poultry raisers and six wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
(38 reference statements)
3
11
0
Order By: Relevance
“…A similar dependency on the local vendors was reported among the backyard poultry raisers in a previous study [74], indicating that this group is a key player for both sectors. These vendors, without any formal training, also prescribed antibiotics for poultry indiscriminately [57,74], contributing to the global concern for antibiotic resistance both for human and animal health [75].…”
Section: Biosecuritysupporting
confidence: 79%
See 2 more Smart Citations
“…A similar dependency on the local vendors was reported among the backyard poultry raisers in a previous study [74], indicating that this group is a key player for both sectors. These vendors, without any formal training, also prescribed antibiotics for poultry indiscriminately [57,74], contributing to the global concern for antibiotic resistance both for human and animal health [75].…”
Section: Biosecuritysupporting
confidence: 79%
“…The study also showed that farmers’ practices and perception of biosecurity, transmission, and prevention of AIV were inconsistent with standard definitions, but were consistent with the recommendations and perceptions of the local vendors of chicks, feed, and medicines, indicating that these vendors heavily influenced farmers’ decisions [57]. A similar dependency on the local vendors was reported among the backyard poultry raisers in a previous study [74], indicating that this group is a key player for both sectors. These vendors, without any formal training, also prescribed antibiotics for poultry indiscriminately [57,74], contributing to the global concern for antibiotic resistance both for human and animal health [75].…”
Section: Biosecuritysupporting
confidence: 56%
See 1 more Smart Citation
“…There are two staff; one is a VFA (Veterinary Field Associate), who performs immunization programs and gives essential preliminary and initial treatment to the animals, and the other is an FAAI (Field Assistants in Artificial Insemination), who just performs artificial impregnation. Yet, without VFA, FAAI additionally performs the duties of a VFA (Rimi et al, 2018). Animal healthcare training could be the best strategy to instruct ranchers for clean administration practice and pre-emptive activities for turning away illnesses.…”
Section: Preventive Veterinary Servicementioning
confidence: 99%
“…Ubiquitous water bodies, rice paddies, and bushland fostering contact with wild bird populations [27,40,43,[61][62][63][64][65][66][67] Commercial poultry Small and medium enterprises…”
mentioning
confidence: 99%